Understanding a STEM teacher's emotions and professional identities: a three-year longitudinal case study - Haozhe Jiang; Ke Wang; Xiaoqin Wang; Xiaohui Lei; Ziyi Huang (SpringerOpen, 2021)
Abstract Background Teacher emotions are sometimes underplayed in the research field of teaching and teacher education. Also, teachers often undergo transformations in their professional identities during education reforms. However, very few studies explore the connections between teacher emotions and their professional identities against the background of education reforms, especially in Asian contexts. There is an increasing emphasis on STEM as an education reform in China and the world, and a deep understanding of STEM teacher emotions and professional identities is necessary in the fast development of STEM education. This study examined how a STEM teacher emotionally constructed her professional identities under the STEM education reform. Methods This is a 3-year longitudinal case study employing a narrative inquiry approach with one STEM teacher in China. Data collection included one in-depth, semi-structured interview, three conversations, personal emotional diaries, and correspondence records. A four-step data analysis was conducted. Results Three major themes reflecting the participant's emotional professional identities emerged, including "an interested but confused learner", "an enthusiastic but nervous explorer", and "an excited but unsatisfied mentor". In the participant's experiences as a learner, explorer, and mentor, positive and negative emotions were always intertwined. These helped construct and shape her professional identities and encouraged her to be the best STEM teacher that she could be. Conclusion This study provides a series of vivid and dynamic pictures of a STEM teacher's emotions and professional identities against the background of STEM education reform in China from a 3-year longitudinal perspective. It also indicates the personal, social, cultural, and contextual factors that could have strong effects on teachers' emotional experiences and the construction of professional identities. Furthermore, this study reveals that three processes (i.e., the process of education changes, the process of creating new or multiple professional identities, and the generation process of teacher emotions) could be intertwined and developed together.